Studying the relationship between angle shooting accuracy and flight time for handball players in Syria - زهرة, ميسم (Latakia University Journal -Medical Sciences Series, 2022)
Shooting is the final movement of all the skillful and tactical efforts that contribute to reaching the goal, and it is one of the basic skills that directly affect the outcome of the match and the boundary between victory and defeat. Shooting near the center of the corner is one of the types of handball. Difficult shooting in terms of performance. The research aims to identify the relationship of flight time to the accuracy of shooting from the corner area for handball players. In this study, the descriptive approach was used to suit the nature of this research, and the sample included the players of the premium class for men in the Syrian Arab Republic (Al Nawaeer Club) for the sports season 2020-2021. And to find out the correlation between flight time and shooting accuracy, the arithmetic mean and the Pearson correlation coefficient were used. Through the results, it was concluded that there is no significant correlation between the variables of shooting accuracy and flight time from the corner area.